Exploring obstacles in language learning: Prospective primary school teacher in Indonesia - Asrial Asrial; Syahrial Syahrial; Dwi Agus Kurniawan; May Subandiyo; Nur Amalina (International Journal of Evaluation and Research in Education (IJERE), 2019)
In the implementation of educational practices, Indonesian is used as the language of instruction. Teacher candidates are prepared to have language competence as their knowledge in carrying out classroom learning. Important language competence is owned by a prospective elementary school teacher to facilitate communication with students and design learning about language. In an effort to improve material understanding and mastery of good language competence, prospective teachers in Primary School Teacher Education have constraints in the learning process in tertiary institutions that are identified based on 9 indicators. These indicators consist of curriculum, practicum activities materials/tools, books/modules, initial abilities of prospective teachers, learning resources from outdoor learning, learning resources from outdoor language learning, learning resources from indoor learning, learning environments, motivating teacher candidates, and the ability to judge yourself. This study uses a qualitative research approach. This study aims to analyze the constraints students face in Indonesian language competence. The sample in this study were students in Primary School Teacher Education with a total of 30 respondents. Data collection using interview and documentation techniques.